Impact of graft loss among kidney diseases with a high risk of post-transplant recurrence in the paediatric population - Stralen, Karlijn J. van; Verrina, Enrico; Belingheri, Mirco; Dudley, Jan; Dušek, Jiří; Grenda, Ryszard; Macher, Marie-Alice; Puretic, Zvonimir; Rubic, Jacek; Rudaitis, Sarunas; Rudin, Christoph; Schaefer, Franz; et al. (Nephrology, dialysis, transplantation, 2013)
Some kidney diseases tend to recur in the renal allograft after transplantation. We studied the risk of graft loss among primary renal diseases known for their high risk of recurrence and compared it with that of patients with hypoplasia and/or dysplasia.Within the European Society of Paediatric Nephrology and European Renal Association and European Dialysis and Transplant Association (ESPN/ERA-EDTA) registry, we studied children from 33 countries who received a kidney transplant before the age of 20 between 1990 and 2009. Patients were censored after 5 years of follow-up and cumulative incidence competing risk analysis was used to calculate survival curves.Patients with focal and segmental glomerulosclerosis (FSGS), haemolytic uraemic syndrome (HUS), membranoproliferative glomerulonephritis Type I or II (MPGN), IgA nephropathy or Henoch Schönlein Purpura (HSP/IgA) or systemic lupus erythomatosus (SLE) underwent pre-emptive transplantation significantly less often than patients with hypoplasia and/or dysplasia. The rate of living donation was lower among patients with FSGS and SLE than in patients with hypoplasia and/or dysplasia. In comparison with hypoplasia and/or dysplasia patients with a risk of 14.4%, the 5-year risk of graft loss was significantly increased in patients with FSGS (25.7%) and MPGN (32.4%) while it was not significantly increased in children with HUS (18.9%), HSP/IgA (16.3%) or SLE (20.3%). One-year graft survival strongly improved among HUS patients from 17.1% in 1995-1999 to 3.6% in 2005-2009 and was not accompanied by a decrease in the number of transplantations.The risk of graft loss is increased among specific causes of renal failure with a high risk of post-transplant recurrence. It seems likely that, due to anticipation of such risk, physicians perform less pre-emptive transplantation and provide fewer grafts from living related donors in patients with these conditions. Improved risk stratification by physicians, resulting in the identification of patients with HUS at higher or lower risk of recurrence, might explain the much improved graft survival rates.